Brassica oleracea L. distribution and ecology in the Iberian atlantic coasts - Fernández Prieto, José Antonio; Herrera Gallastegui, Mercedes (Lazaroa, 2014)
The distribution and ecology of Brassica oleracea in the atlantic coasts of Iberian Peninsule are studied. A new association or nitrified maritime cliffs is described: Crithmo-Brassicetum oleraceae. This community has been included in the Alliance Crithmo-Armerion due to the high presence of halophitic species.